Between session reliability of intramuscular electromyography for segments of gluteus medius and minimus during gait and stepping tasks. (August 2019) - Green, R.A.; Pizzari, T.; McClelland, J.; Zacharias, A.; Huynh, P.; Weerakkody, N.; Semciw, A.I.
Abstract: Between-session reliability of electromyographic data is important for confidence in interpreting the role of muscles in functional tasks but critical if these data are to be compared before and after an intervention that seeks to change pathological patterns of muscle activity. The gluteus medius (GMed) and minimus (GMin) are known to have functionally discrete segments that are highly active during stance phase of gait and stepping tasks. This study measured the between-session reliability of activity patterns, mean amplitudes and time to peak (TTP) activity of these muscle segments. Intramuscular electrodes were placed in 3 segments of GMed and 2 segments of GMin in 10 healthy young adults for each of two testing sessions held two weeks apart. Participants completed six repetitions of comfortable speed walking trials, step-up and step-down tasks with activity patterns for each muscle segment time- and amplitude-normalized and averaged across trials. Re-test reliability for was high for activity patterns (coefficient of mean correlation ranging from 0.890 to 0.998) across all tasks and muscle segments and only two pairwise comparisons showing differences in amplitude between sessions. With standardized data collection and analysis procedures, GMed and GMin muscle segment activity patterns show good between-session reliability for weightbearing tasks.